Gambaran Kualitas Kerja Karyawan PT. Bank Syariah Indonesia KCP Wonomulyo Polewali Mandar - Nurfitriani Fitri (Institut Agama Islam Negeri Parepare, 2022)
Performance is the result of work in quality and quantity that can be achieved by an employee in carrying out his main duties and functions as an employee in accordance with the responsibilities assigned or given to him (Fauzi, 2020). Discusses employee performance, which is inseparable from the factors that affect employee performance, namely the quality of employee work. According to Flippo (Amaliyyah et al., 2021) work quality is a result that can be measured by the effectiveness and efficiency of a job carried out by human resources or other resources in achieving company goals or objectives properly and efficiently. Indonesian Islamic banks are generally required to be able to compete with conventional banks by improving the quality of work of their employees, including moving the wheels of the Indonesian economy (Umardani & Muchlish, 2016). In order to be able to face competition in the banking world, companies need to have advantages, one of which is by improving their human resources (Sinaga et al., 2021). Bank Syraiah Indonesia KCP Wonomulyo Polewali Mandar has 18 active employees at the moment, where researchers are interested in knowing how the quality of these employees is described and how much the average level of work quality is owned by employees. Therefore, the researcher raised the title, which is a description of the quality of work of employees of PT. Bank Syariah Indonesia KCP Wonomulyo Polewali Mandar. This research uses a type of quantitative approach with sampling, namely the saturated sampling technique in which all the population is used as a sample (Unaradjan, 2019). This research was conducted on 18 active employees who were then analyzed using descriptive analysis. The results of the study were that more subjects were male, namely 10 people (55.6%), the most subjects were those who worked 6-10 years, namely 8 people (44.4%), and the most subjects were aged between 26-30 years, namely 7 people (38.8%). As for the quality of work of employees of PT. Bank Syariah Indonesia KCP Wonomulyo Polewali Mandar is dominant in the high category, namely 8 people (58.89%).